\(\displaystyle{4}\sqrt{{2}}+{2}{\left(\sqrt{{36}}-\sqrt{{8}}\right)}={4}\sqrt{{2}}+{2}{\left({6}-\sqrt{{{4}\times{2}}}\right)}\)

\(\displaystyle={4}\sqrt{{2}}+{12}-{4}\sqrt{{2}}\)

\(\displaystyle={\left({4}\sqrt{{2}}-{4}\sqrt{{2}}\right)}+{12}\)

=0+12

=12

The answer:

\(\displaystyle{4}\sqrt{{2}}+{2}{\left(\sqrt{{36}}-\sqrt{{8}}\right)}={12}\)

\(\displaystyle={4}\sqrt{{2}}+{12}-{4}\sqrt{{2}}\)

\(\displaystyle={\left({4}\sqrt{{2}}-{4}\sqrt{{2}}\right)}+{12}\)

=0+12

=12

The answer:

\(\displaystyle{4}\sqrt{{2}}+{2}{\left(\sqrt{{36}}-\sqrt{{8}}\right)}={12}\)